Experiences of Female Patients Diagnosed with Rheumatoid Arthritis in a Public Hospital in Paraguay: Qualitative Study - Sosa Aquino, Olga; Sosa Gómez, Oscar Misael; Genes Soto, Fernando; Burguez, Niselli; Ramos Duarte, Liliana Elizabeth; Zanina, Tathiana Larisse (Medicina Clínica y Social, 2024)
Introduction: Rheumatoid arthritis is a condition characterized by joint pain, fatigue, difficulty in performing daily activities, persistent inflammation, and progressive tissue damage. According to previous studies, rheumatoid arthritis is significantly more common in women than in men. Objective: To analyze the experiences of women with rheumatoid arthritis, patients of a public hospital in the city of Asunción during the year 2024. Methodology: A qualitative study with a phenomenological design. Fifteen women with rheumatoid arthritis who receive care at a public hospital in Asunción, Paraguay, were interviewed. Results: Three central themes were identified: first, impact on daily life, where patients must adapt their daily routines due to the symptoms of the disease; second, emotional and social management, in which the support of family and friends is essential to facilitate the management of the disease and provide emotional support; and third, treatment and disease management, highlighting that the use of medication is crucial to controlling symptoms and reducing the progression of rheumatoid arthritis. Conclusions: Rheumatoid arthritis significantly impacts daily life, emotional management, and treatment in women, underscoring the need for a comprehensive approach that includes routine adaptations, constant social support, and appropriate use of medication to improve their quality of life.